Crystal Palm Sugar Yield Optimization and Its Chemical and Sensory Characteristics - Marwati; Irma Febriandini; Krishna Purnawan Candra; Yuliani; Hamka Nurkaya (Food Science and Technology Journal (Foodscitech), 2023)
Crystal palm sugar (CPS) is crystal brown sugar produced from palm tree sap. The quality of CPS depends on the quality/freshness of the sap, while the sap quality depends on the tapping method and its freshness. This study aimed to determine the appropriate sap tapping time of Arenga palm (Arenga pinnata) for raw material in CPS processing. The sap tapping time was carried out at 3, 6, 9, and 12 hours, each with four replications. Sap tapping was done by adding five grams of sodium bicarbonate into the sap container. Parameters observed were sap pH, yield, chemical properties (moisture content, ash content, and reducing sugar content), and sensory properties (color, aroma, texture, and taste) of the CPS. The data were processed by ANOVA and polynomial regression. The results showed that sap tapping time significantly affected (p<0.05) the sap pH and reducing-sugar content of CPS, but not (p>0.05) the yield, water content, ash content, and sensory response of CPS. However, using quadratic polynomial regression shows that CPS yield is optimum by processing the palm sap at about seven hours of tapping time, i.e., 14.56% and 12.47% for coarse and fine CPS, respectively. The sap pH obtained from the seven hours of tapping time was 6.8-7.1. The CPS has a reducing sugar content of 26.94% and overall hedonic characteristics of moderately like. The hedonic quality characteristics of the CPS are typical palm sugar for aroma, slightly brown for color, slightly hard for texture, and sweet for taste.